Pricing Decisions and Online Channel Selection Strategies in Dual-Channel Supply Chains considering Block Chain - Qiang Li; Huanling Li (Discrete Dynamics in Nature and Society)
Pricing decisions and online channel selection strategies are playing an increasingly important role in e-commerce. In this paper, we consider two different types of dual-channel supply chain sales models, namely, an online direct + online distribution sales model consisting of an online direct sales channel and online distribution sales channel and an online direct + delegation sales model consisting of an online direct sales channel and an online delegation sales channel. By introducing the customer sensitive coefficient and block chain technology into these dual-channel supply chain sales models, we analyzed pricing decisions and online channel selection strategies in dual-channel supply chains in terms of the adoption and nonadoption of block chain technology. In the two different dual-channel sales models, the results showed that (1) without block chain technology, retail prices increase when the manufacturer’s unit retail cost increases; (2) with block chain technology, retail prices are higher than those of sales models that do not adopt block chain technology; and (3) with block chain technology, the manufacturer should choose the online direct + delegation sales model to sell its products.